Value Analysis in Construction Projects with BIM implementation: A Systematic Review - Altaf, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
The policymakers in the construction sector prefer to limit costs, which is a vital step for achieving project success and increasing their worth. Value engineering (VE) is an efficient technique to project cost control without performance disruption. Many studies have identified the significant impact of Building information modelling (BIM) and VE on cost optimisation and performance improvement for construction projects, and research into combining BIM and VE for a higher synergistic impact is restricted in the AEC industry. This systematic study aims to emphasise the integration of the comprehensive and autonomous approach of BIM and VE for reducing costs with original performance. The corresponding literature was retrieved from the database Scopus. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach was used to retrieve 106 publications, and 12 papers were left for further evaluation. The VE with the use of BIM is emphasized in the evaluated papers. The BIM approach can facilitate quantity estimate and analysis of various project values. Data acquisition, on the other hand, remains a major hurdle to executing VE using BIM. A BIM Library consisting of the relevant VE data parameter is needed, and a schema like IFC and COBie is required to support VE data interchange. Â© 2021 IEEE.